2019
DOI: 10.1093/ntr/ntz156
|View full text |Cite
|
Sign up to set email alerts
|

Latent Classes of Nicotine Beliefs Correlate with Perceived Susceptibility and Severity of Nicotine and Tobacco Products in US Young Adults

Abstract: Background Pervasive misperceptions about nicotine may influence uptake of quit smoking aids and the impact of policies addressing nicotine as a tobacco product constituent. Methods Latent class analyses were conducted using four items on nicotine beliefs asked of 4037 adults aged 18–40 in wave 9 (February–March 2016) of the Truth Initiative Young Adult Cohort Study. Confirmatory factor analyses identified three factors from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
2
9
1
Order By: Relevance
“…Four items addressing nicotine beliefs at Wave 9 were included in latent class models; detail on these analyses have been published elsewhere (Villanti et al, 2019a). Three items assessed nicotine's role in causing disease (i.e., "Nicotine is a cause of cancer"; "According to you, how large a part of the health risks of cigarette smoking comes from the nicotine itself?…”
Section: Nicotine Beliefs Latent Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Four items addressing nicotine beliefs at Wave 9 were included in latent class models; detail on these analyses have been published elsewhere (Villanti et al, 2019a). Three items assessed nicotine's role in causing disease (i.e., "Nicotine is a cause of cancer"; "According to you, how large a part of the health risks of cigarette smoking comes from the nicotine itself?…”
Section: Nicotine Beliefs Latent Classmentioning
confidence: 99%
“…Our previous work in U.S. adults aged 18-40 identified that people cluster into four latent classes based on their beliefs about nicotine: those who believe that nicotine causes cancer and plays a large part in smoking risks (Class 1); those who share the belief about nicotine's large part in causing smoking health harms, but were differentiated from Class 1 by "don't know" responses to nicotine's addictiveness and role in cancer (Class 2); those who believe that nicotine plays no role or a small part in health risks (Class 3); and those who believe that nicotine plays no role or a small part in health risks and that none or a very small part of cancer is caused by nicotine (Class 4; Villanti et al, 2019a). The goal of the current study was to examine whether these latent classes were associated with susceptibility and curiosity to use tobacco and tobacco use behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These beliefs are associated with perceived harm of nicotine and tobacco products and correlated with sociodemographic predictors of smoking. 20 These findings may help us to identify specific beliefs or groups to be targeted by public education efforts on nicotine.…”
Section: Perceptions and Communicationsmentioning
confidence: 99%
“…These authors recommend key elements of public education efforts to correct misperceptions of nicotine in order to maximize the potential benefits of a nicotine reduction standard. An empirical analysis 20 models latent classes of nicotine beliefs among US young adults and identifies four classes of beliefs, with the largest class believing that nicotine plays a major role in smoking risk. These beliefs are associated with perceived harm of nicotine and tobacco products and correlated with sociodemographic predictors of smoking.…”
Section: Perceptions and Communicationsmentioning
confidence: 99%
“…4,5 There are strong correlations between nicotine beliefs and the perceived harms of nicotine and tobacco products. 6 Given these common misperceptions about nicotine, a low nicotine product standard has potential to further confuse consumers about tobacco product risks in the absence of public education efforts.…”
Section: Public Misperceptions Of the Health Risks Of Nicotinementioning
confidence: 99%